Pengembangan Senam Rentak Melayu Untuk Meningkatkan Kemampuan Motorik Kasar Anak Usia 5-6 Tahun di TK Barunawati II Kota Dumai - Cahya Syafitri; Nurlita Nurlita; Defni Satria (Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to develop Malay Rentak Gymnastics to improve gross motor skills of children aged 5-6 years. The type of research used is research and development (Research and Development). The steps taken are potential and problems, data/information collection, design, design validation, design revision, and product trials. Data collection techniques with observation, distributing questionnaires, and documentation. The instrument used was a questionnaire to validate Malay Rentak Gymnastics from media experts, material experts, gymnastics experts and educators. The data analysis technique used is a quantitative descriptive analysis technique. In the study, it was obtained that the validation of media experts was 90.44%